Influence of knowledge on practice of deaf culture among students with hearing impairment in the South-west, Nigeria (2022)
The study examined the level of knowledge about the practice of deaf culture of students with hearing impairment in the South-West, Nigeria. The study adopted the descriptive survey research design. A purposive sampling technique was used to select 673 students with hearing impairment in 12 integrated schools in six states of the South-West. A self-designed instrument tagged “Test of Knowledge of Students with Hearing Impairment on Deaf Culture ”(r=0.73) was used for data collection. Data collected were analysed using descriptive statistics of frequency count and percentage and inferential statistics of t-test. The findings of the study revealed that students with hearing impairment have a fair knowledge of deaf culture (1.61). It was also revealed that there was a significant difference between the level of knowledge about the deaf culture of students with hearing impairment with deaf parents and those with hearing parents (t=3.83; df=671). There was a significant difference between knowledge about deaf culture among students with pre-lingua! and those with post- lingual hearing loss (1=6.94: df=671). There was also a significant difference between the level of knowledge about deaf culture of male and female students with hearing impairment (t=3.94). Knowledge about deaf culture was greatly determined by parents’ hearing status, the onset of hearing impairment and students’ gender. There is an urgent need to incorporate deaf culture into the educational system in the integrated secondary schools to meet the cultural, social and linguistic needs of students with hearing impairment.